Noncommutative U(1) extension to the standard model su(3) ⊗ su(2) ⊗ u(1) ⊗ u(1) and dark mater - khelifi cheref eddine. Enc/ Boussahel Mounir. (Université Mohamed Boudiaf - M’Sila, 2024)
In this memo, we will compile some ideas from various research studies with the aim of examining the impact of treating the new, extension as an interaction mediator between dark matter particles, which interact with real matter indirectly due to the mixing term with the ordinary photon, on the mass of this new boson. On the other hand, we will also present a new mathematical framework, namely non-commutative geometry, in a simplified manner.